2011
DOI: 10.1039/c1ob05307h
|View full text |Cite
|
Sign up to set email alerts
|

Altering intercomponent interactions in a photochromic multi-state [2]rotaxane

Abstract: Rotaxanes have attracted much attention because of their challenging constructions and potential applications. In this paper, a multi-state [2]rotaxane, in which a dithienylethene-functionalized dibenzo-24-crown-8 macrocycle was interlocked onto a thread component bearing a 4-morpholin-naphthalimide fluorescent stopper and two distinct recognition sites, namely, dibenzylammonium and N-methyltriazolium recognition sites, was prepared and studied. By introducing a dithienylethene photochrome into the macrocycle … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
24
0
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 59 publications
(25 citation statements)
references
References 36 publications
0
24
0
1
Order By: Relevance
“…The 1 H NMR spectrum of 1 in CDCl 3 is shown in Figure 1. We analyzed the 1 H NMR spectrum of 1 in comparison with our previously reported rotaxanes,14b, c, 15a, 16 and found that the BODIPY‐functionalized DB24C8 macrocycles predominately resided on the DBA recognition sites in 1 . The chemical shifts at δ =8.34, 8.05, and 7.12 ppm indicated the existence of the OPV moiety in 1 .…”
Section: Resultsmentioning
confidence: 98%
“…The 1 H NMR spectrum of 1 in CDCl 3 is shown in Figure 1. We analyzed the 1 H NMR spectrum of 1 in comparison with our previously reported rotaxanes,14b, c, 15a, 16 and found that the BODIPY‐functionalized DB24C8 macrocycles predominately resided on the DBA recognition sites in 1 . The chemical shifts at δ =8.34, 8.05, and 7.12 ppm indicated the existence of the OPV moiety in 1 .…”
Section: Resultsmentioning
confidence: 98%
“…Firstly, we analyzed the 1 H NMR spectra of rotaxanes 1 and 2 (Figure 1). Comparison between the 1 H NMR spectra of rotaxanes 1 and 2 and our previously synthesized rotaxanes4c, f, 5b, 7b revealed that the DB24 C8 macrocycles predominately reside on the DBA recognition sites in rotaxanes 1 and 2 . The 1 H NMR spectra (Figure 1) of [4]rotaxanes 1 and 2 showed similar patterns in CD 3 COCD 3 , with no significant differences other than the absence of the peaks of H a , H b , H c , and H d of the Fc unit in the spectrum of [4]rotaxane 2 .…”
Section: Resultsmentioning
confidence: 79%
“…[ 59 ] When reached the photostationary state (PSS) after irradiation for 2 min, an isosbestic point at 310 nm emerged indicated that this is a unimolecular process. [ 60 ] Reversely, when visible light ( λ > 500 nm) was imposed, the purple 1c solution returned to the original colorless solution, indicating that a photocycloreversion changed from 1c to 1o . The cyclization and cycloreversion quantum yields were measured to be 0.20 and 0.017, respectively, with 1,2‐bis(2‐methyl‐5‐phenyl‐3‐thienyl)perfluorocyclopentene as reference.…”
Section: Resultsmentioning
confidence: 99%